Patience and Work Engagement among Islamic Bank Employees - Endro Puspo Wiroko; Muhammad Rifky Fadillah (Jurnal Psikologi Islam dan Budaya, 2020)
This research investigates Islamic bank employees’ work engagement and its correlation to patience. Work engagement is fulfilling and positive state of mind that is characterized by vigor, dedication, and absorption. Patience is a coping strategy which involves rational thinking, self-acceptance, self-control, and effort. By using accidental sampling, final participants were 169 employees working in Islamic bank who were varied in age, job position, employment status, tenure, educational background, and work location. Data was gathered by using two measures: The Utrecht Work Engagement Scale and Patience scale and it were analyzed using Pearson correlation. Patience is found to relate positively with work engagement (r = .603). Islamic bank management may conduct training about patience to enhance their employees’ engagement.